Pengembangan Bahan Ajar “Modul Pembelajaran” IPAS Berbasis Saintifik pada Materi “Energi dan Perubahannya” untuk Meningkatkan Pemahaman Konsep Energi Siswa Kelas IV SDN 1 Gontoran - Hildah Dwipa Nurahma; Muhammad Makki; Prayogi Dwina Angga (Mataram University, 2026)
Fourth-grade students were selected as the research subjects because they are in the concrete operational stage and therefore require teaching materials that are engaging, contextual, and tailored to their characteristics. The topic of energy and its transformations was chosen because it is an component of IPAS that students often struggle to understand, particularly when it comes identifying the forms and transformations of energy. This study aims to produce a valid, practical, and effective science-based IPAS learning module to improve students’ understanding of energy concepts. This study employed the (R&D) method using the ADDIE development model. The results showed that the module’s validity was very high, with 89,23% validity rating from media experts and a 94,11% validity rating from content experts. The practicality level in the small-group test achieved a percentage of 77,7% meeting the “practical” criterion, while the large-group test achieved a percentage of 83,43% meeting the “highly practical” criterion: teacher feedback also achieved a percentage of 97,9% meeting the “highly practical” criterion. The N-Gain result was 0,5686 (56.8579%), meeting the “effective” criterion. Therefore, the science-based IPAS learning module teaching materials are valid, practical, and effective for improving the understanding of energy concepts among fourth-grade students at SDN 1 Gontoran.